Kegiatan TUR Pemanduan Sejarah Sebagai Wisata Edukasi Dan Promosi Rute Pasar 16 Kolaborasi Bersama PLGGoodGuide - Rahman, M. Arief; Saputra, Muhammad Yogi (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
Pasar 16 Ilir in Palembang has high historical and cultural value as one of the oldest trading centers in the city. However, the lack of public understanding, especially the younger generation, of the historical value of Pasar 16 Ilir is an issue that needs to be addressed so that this cultural heritage is maintained. This community service program aims to increase awareness and appreciation of local history through educational and interactive historical guided tours. This activity is carried out in collaboration with PLGGoodGuide, a local community that acts as a tour guide, and involves the participation of traders and craftsmen at Pasar 16 Ilir. The methods used in this program include interactive guiding approaches, direct observation, and surveys to measure participants' understanding and satisfaction. The results showed an increase in participants' knowledge and appreciation of Palembang's history and culture, as well as a positive impact on the local economy through the promotion of products and businesses in the market. This collaboration succeeded in creating an educational tourism model that can be used as a reference for similar activities in other places, supporting cultural preservation, and strengthening the attractiveness of historical tourism in Palembang.